2014
DOI: 10.1186/1477-7819-12-191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the POSSUM, P-POSSUM and E-PASS scores in the surgical treatment of hilar cholangiocarcinoma

Abstract: BackgroundThe Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM) model, its Portsmouth (P-POSSUM) modification and the Estimation of physiologic ability and surgical stress (E-PASS) are three surgical risk scoring systems used extensively to predict postoperative morbidity and mortality in general surgery. The aim was to undertake the first study of the predictive value of these models in patients undergoing surgical treatment of hilar cholangiocarcinoma.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
1
18
1
2
Order By: Relevance
“…The ability of the E-PASS models was high to predict 16 These findings support the E-PASS models having a high predictive power in this field.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The ability of the E-PASS models was high to predict 16 These findings support the E-PASS models having a high predictive power in this field.…”
Section: Discussionsupporting
confidence: 76%
“…Another limitation is that this study was only performed in Japan. Although the high predictive power of E-PASS for hilar carcinoma was previously demonstrated in China, 16 validation studies are desirable in western countries.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Postoperative morbidity and mortality rates are objective measures of outcomes that can be used to modify behavior and assess the quality of care. Previous studies have evidenced the important role of the POSSUM system as a predictor of postoperative morbidity and mortality 5,9,10 . A systematic review of the literature that evaluated POSSUM and its variants in patients undergoing surgery for colorectal cancer showed that the POSSUM score was able to predict morbidity in a reliable way and the P-POSSUM was the most accurate predictor of mortality, even when compared with CR-POSSUM 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional histology relies on microscopic examination of a specimen obtained from biopsy or surgery, which is usually time consuming due to the complicated sample preparation procedures including fixation, sectioning and staining. The frozen sections of surgical margin are assessed during hepatocellular carcinoma or cholangiocarcinoma surgery to achieve a R0 resection (complete resection with microscopic examination of margins showing no tumor cells) [5]. Re-resection and/or re-anastomosis must be performed if the surgical margin is tumor positive, leading to the prolonged operation time.…”
Section: Introductionmentioning
confidence: 99%